Kebijakan Pembagian Dividen Perusahaan BUMN Indonesia Periode 2011-2016 - Siti Nurainul Jannah (Jurnal Ekonomi Akuntansi dan Manajemen, 2018)
The purpose of this study is to analyze the factors that influence the dividend payout policy on BUMN companies listed in Indonesia Stock Exchange period 2011-2016. The independent variables used in this research are profitability, liquidity, asset growth, and company size. The method used is the method of quantitative research and the object of research is a state-owned company listed on the Indonesia Stock Exchange. The data used in this study was secondary data in the form of financial statements obtained by data collection techniques using documentation method. The sample used in this research is twelve companies using purposive sampling method. The technique of data analysis using was multiple linear regression analysis using SPSS test tool. The results showed that all independent variables together positive effect on dividend policy. While the t-test results show that only Profitability variables that have a positive and significant influence toward the dividend payout policy. The independent variables liquidity, asset growth, and company size have a positive and insignificant effect on dividend policy. The dividend payout policy is one of the main concerns of the stakeholders. However, this study uses only four independent variables to analyze the factors that influence the dependent variable. The magnitude of influence of all independent variables in this study only 33% and the rest much influenced by other variables outside in this study. Keywords: dividend payout policy, profitability, liquidity, asset growth, company size